Disaggregating Foregin Aid: An Assessment of the Impact of Health Aid on Infant and Child Mortality in Selected Asia and the Pacific Countries (2002- 2017) - Mayo, Charlon (Archīum Ateneo, 2020)
Over the years, several studies have explored the relationship of foreign aid and economic growth, but there is limited study assessing the impacts of disaggregated health aid on population health. This study utilizes health production function to assess the impact of health aid and other social, economic, and environmental variables to population health, using panel data of ten selected countries from Asia and the Pacific from 2002-2017. The study also reviews health aid programs that shaped health system in some countries in the region. The fixed effects model results indicate that health aid, GDP per capita, and food production index significantly reduce infant, neonatal, and under-five mortality in selected countries in Asia and the Pacific region, while factors such as population and urbanization have also significant role in the health status of the population. The findings of the study concur with other literature, which conclude that health-specific aid significantly improves the health outcomes of the countries. The paper concludes with suggestions for future research and some evidence-based policy recommendations.